2017
DOI: 10.1111/epi.13740
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐responsive neurostimulation in patients with medically intractable mesial temporal lobe epilepsy

Abstract: SUMMARYObjective: Evaluate the seizure-reduction response and safety of mesial temporal lobe (MTL) brain-responsive stimulation in adults with medically intractable partial-onset seizures of mesial temporal lobe origin. Methods: Subjects with mesial temporal lobe epilepsy (MTLE) were identified from prospective clinical trials of a brain-responsive neurostimulator (RNS System, NeuroPace). The seizure reduction over years 2-6 postimplantation was calculated by assessing the seizure frequency compared to a preim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
239
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(248 citation statements)
references
References 39 publications
7
239
1
1
Order By: Relevance
“…Several other seizure-detection devices have appeared within the last decade, some employing EEG 2,10,17,21,22 and some employing other technologies, such as EMG/accelerometry, 23,24 heart rate variability, 25 electrodermal activity, or a combination of these. Several other seizure-detection devices have appeared within the last decade, some employing EEG 2,10,17,21,22 and some employing other technologies, such as EMG/accelerometry, 23,24 heart rate variability, 25 electrodermal activity, or a combination of these.…”
Section: Discussionmentioning
confidence: 99%
“…Several other seizure-detection devices have appeared within the last decade, some employing EEG 2,10,17,21,22 and some employing other technologies, such as EMG/accelerometry, 23,24 heart rate variability, 25 electrodermal activity, or a combination of these. Several other seizure-detection devices have appeared within the last decade, some employing EEG 2,10,17,21,22 and some employing other technologies, such as EMG/accelerometry, 23,24 heart rate variability, 25 electrodermal activity, or a combination of these.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, follow‐up studies reported that patients with focal epilepsy responded differently depending on seizure focus (Table ). TLE patients treated with RNS had a median seizure reduction of 70%, and the responder rate was 66% . In patients with neocortical epilepsy, the median reduction was 55%, and the responder rate was 77% …”
Section: Neurostimulation To Treat Epilepsymentioning
confidence: 99%
“…RNS efficacy was reported at 1 and 2 years postimplantation . Specific efficacy in mTLE was reported in year 6, and seizure freedom rate was based on the previous 6 months . Year 6 efficacy in neocortical epilepsy was based on the previous 3 months .…”
Section: Neurostimulation To Treat Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…These devices provide therapy by disrupting epileptogenic networks. They can reduce seizure frequency by 68%–76%, if stimulation continues for 5 years or more 9. In addition, disconnective surgeries (eg, corpus callosotomy and multiple subpial transections) are considered palliative, as epileptogenic foci are not removed.…”
Section: Introduction/backgroundmentioning
confidence: 99%